2020
DOI: 10.4103/jfmpc.jfmpc_585_20
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, experience, and practice of physicians regarding adult gastroesophageal reflux disease (GERD) in Riyadh, Saudi Arabia

Abstract: Background and Aims: Gastroesophageal reflux disease (GERD) was frequently managed by residents as they are the first physician who encounter the patient. This study was conducted to explore the knowledge and practice of physicians in the treatment of GERD and to compare between residents and consultants regarding their knowledge and practice. Methodology: A cross-sectional study, self-administered questionnaire. Results: Esophagogastroduoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Comparing the current data to the previous local studies is challenging due to the lack of similar study designs, lack of standard knowledge tools, and small sample size of the previous studies. [ 19 20 ] Nevertheless, the inadequate knowledge observed in the current study is not surprising. A local study that compared GERD management by residents and consultants in three governmental hospitals in Riyadh found that 41.3% of the residents and 27.8% of the consultants were not aware of any guidelines for GERD management patients.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Comparing the current data to the previous local studies is challenging due to the lack of similar study designs, lack of standard knowledge tools, and small sample size of the previous studies. [ 19 20 ] Nevertheless, the inadequate knowledge observed in the current study is not surprising. A local study that compared GERD management by residents and consultants in three governmental hospitals in Riyadh found that 41.3% of the residents and 27.8% of the consultants were not aware of any guidelines for GERD management patients.…”
Section: Discussionmentioning
confidence: 57%
“…A local study that compared GERD management by residents and consultants in three governmental hospitals in Riyadh found that 41.3% of the residents and 27.8% of the consultants were not aware of any guidelines for GERD management patients. [ 19 ] Internationally, studies assessing GERD management knowledge in family physicians are limited and do not focus on the residents. [ 18 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations